STUDI KOMPARATIF TIMBULAN SAMPAH DI WILAYAH URBAN DAN SUBURBAN DI JAWA TIMUR - Milasari (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Municipal solid waste generation poses a major environmental challenge in rapidly developing regions. This study compares daily waste generation between urban and suburban areas in East Java Province, Indonesia, using a quantitative approach with spatial analysis. Descriptive analysis was employed to examine waste generation patterns, Moran’s I was used to detect spatial autocorrelation, and Geographically Weighted Regression (GWR) was applied to assess localized socio-economic influences. The results reveal significant differences between urban and suburban areas. Major cities such as Surabaya and Malang produce higher per-capita waste compared to suburban areas including Pasuruan and Lamongan. Organic waste dominates overall composition, while urban areas exhibit higher proportions of plastic and paper waste. Spatial analysis identifies concentrated waste generation along the Surabaya–Sidoarjo–Gresik–Malang corridor, confirmed by significant Moran’s I values. GWR findings indicate spatially varying determinants: income strongly influences waste generation in core urban centers, population density plays a key role in transitional zones, and household size exerts greater effects in suburban areas. These findings emphasize the need for place-based policies and inter-regional collaboration to support sustainable waste management in East Java.